Evaluating The Impact of Structured Training Programs on Stress Reduction Among College Students - T., Thenmozhi; Kumar, M. Senthil; Sanjaykumar, Swamynathan (Journal of Neonatal Surgery, 2025)
Stress has become a significant concern among college students, impacting their academic performance and overall well-being. This research aims to examine the effects of high-intensity and moderate-intensity exercise on stress reduction in college students. Sixty participants were randomly assigned to three groups: Experimental Group I (high-intensity interval training), Experimental Group II (moderate-intensity continuous training), and a control group (no exercise intervention). Stress levels were assessed using a standardized questionnaire before and after a 12-week period. ANOVA was used to analyse the differences in pre- and post-test stress scores, with a significance level set at 0.05. Results revealed substantial reductions in stress for both exercise groups, with mean differences of -4.73 and -4.67 for high- and moderate-intensity groups, respectively (p < 0.0001). The control group showed a minimal reduction of -0.30 (p = 0.0027), which was not significant. These findings suggest that both high- and moderate-intensity physical activities are effective in alleviating stress among college students. The study supports the integration of exercise into campus wellness programs to improve mental health. Further research could investigate the long-term effects of different exercise types and their impact on various stress sources.